Effect of a health education program about COVID-19 on the knowledge, attitude, and practices of paramedical students in Egypt: an interventional study - Osama Wassef; Souad Elgendy; Abd E. Dawah; Mona Elawady; Enjy Khedr (AOSIS, 2023)
Background: In December 2019, an outbreak of novel coronavirus disease 2019, caused by severe acute respiratory syndrome coronavirus 2, has been reported in China. Objective: This study aims to assess the knowledge, attitude, and practices (KAP) of Benha Health Technical Institute (BHTI) students and to evaluate the impact of a health education program about COVID-19 on their KAP. Methods: This is an interventional study that recruited 398 students from BHTI and was conducted in 3 phases. Firstly, an assessment of students' KAP was done using a structured questionnaire concerning COVID-19. Secondly, an education program about COVID-19 was conducted. Lastly, the reassessment of KAP was carried out using the same questionnaire after one month. Results: The median knowledge, attitude, and practice scores among the studied students in the pre-interventional stage were 12, 15, and 26 which had significantly increased to 15, 16, and 28 respectively after the intervention. The knowledge score of the participants was significantly affected by students' age and grade of education; the attitude score was affected by age, gender, and grade of education, while the practice score was only affected by participants' age. Conclusion: The educational program significantly increased the KAP of BHTI students.